2017
DOI: 10.1007/s40279-017-0730-2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Resistance Training on Swimming Performance: A Systematic Review

Abstract: Future research is needed with respect to the effects of long-term resistance-training interventions on both technical parameters of swimming and overall swimming performance. The results of such work will be highly informative for the scientific community, coaches and athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
99
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 70 publications
4
99
0
9
Order By: Relevance
“…To date, no multi-joint isometric test for upper body pulling ability has been validated. Given the importance of upper body pulling ability in various sports such as kayaking [16] and swimming [17], it is important for practitioners to use a validated and reliable test to assess the athletes' upper body pulling force-time curve characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no multi-joint isometric test for upper body pulling ability has been validated. Given the importance of upper body pulling ability in various sports such as kayaking [16] and swimming [17], it is important for practitioners to use a validated and reliable test to assess the athletes' upper body pulling force-time curve characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In several sports, CT is a usual method of training, as it combines the specific motions of sports, such as swimming or running, with resistance training to obtain gains in several actions/tasks crucial for increase sport performance [48][49][50][51]. Our search revealed that among the studies on CT intensity, only a few reported data on professional athletes [37,42,44].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of RT on swimming performance are a frequently debated topic. 58 performance; however, more longitudinal studies are needed. RT also plays a vital role in reducing the occurrence of injuries, 60 particularly in youth athletes.…”
Section: Rt Cross-training Activities and Risk Of Early Specializationmentioning
confidence: 99%